Nursery schools or nursery classes? Choosing and failing to choose between policy alternatives in nursery education in England, 1918–1972. Issue 1 (2nd January 2016) - Palmer, Amy
Abstract : This article analyses early years education policy in England from 1918 to 1972, applying the theoretical ideas of John Kingdon. Throughout this period, the educational needs of young children were a low political priority, but they did occasionally rise on the agenda. When the issue gained prominence, politicians considered two key policy alternatives for potential investment: the expensive, self-governing nursery school, orientated towards promoting children's physical health, and the cheaper nursery class, attached to an infant school, perhaps better at easing transition to formal education. After an initial period of damaging indecisiveness, the choice fell first on nursery schools and then on nursery classes. The reason that such fundamental changes in approach were possible was that an underlying lack of political commitment meant policies were only ever partially implemented. This chaotic pattern of development has had a damaging effect on the coherence of early years services offered today.